Long‐term stability, functional competence, and safety of microencapsulated specific pathogen‐free neonatal porcine Sertoli cells: a potential product for cell transplant therapy. (2nd July 2015) - Luca, Giovanni; Mancuso, Francesca; Calvitti, Mario; Arato, Iva; Falabella, Giulia; Bufalari, Antonello; De Monte, Valentina; Tresoldi, Enrico; Nastruzzi, Claudio; Basta, Giuseppe; Fallarino, Francesca; Lilli, Cinzia; et al.
Abstract Background Porcine Sertoli cells (pSCs) have been employed for cell therapy in pre‐clinical studies for several chronic/immune diseases as they deliver molecules associated with trophic and anti‐inflammatory effects. To be employed for human xenografts, pSCs products need to comply with safety and stability. To fulfill such requirements, we employed a microencapsulation technology to increase pre‐transplant storage stability of specific pathogen‐free pSCs (SPF‐pSCs) and evaluated the in vivo long‐term viability and safety of grafts. Methods Specific pathogen free neonatal pigs underwent testis excision under sterility. pSCs were isolated, characterized by immunofluorescence (IF) and cytofluorimetric analysis (CA) and examined in terms of viability and function [namely, production of anti‐müllerian hormone (AMH), inhibin B, and transforming growth factor beta‐1 (TFGβ‐1)]. After microencapsulation in barium alginate microcapsules (Ba‐MC), long‐term SPF‐pSCs (Ba‐MCpSCs) viability and barium concentrations were evaluated at 1, 24 throughout 40 h to establish pre‐transplant storage conditions. Results The purity of isolated pSCs was about 95% with negligible contaminating cells. Cultured pSCs monolayers, both prior to and after microencapsulation, maintained high function and full viability up to 24 h of storage. At 40 h post‐encapsulation, pSCs viability decreased to 80%. Barium concentration in Ba‐MCpSCs lagged below the normal maximum daily allowance and was stable for 4 months in mice with no evident side effects. Conclusions Such results suggest that this protocol for the isolation and microencapsulation of pSCs is compatible with long‐haul transportation and that Ba‐MCpSCs could be potentially employable for xenotransplantation.